Application of RFID in Aviation Industry: An Exploratory Review - Mishra, Alok; Mishra, Deepti (Promet - Traffic&Transportation, 2012)
Recently, Radio Frequency Identification (RFID) has received considerable attention and is considered to be the next wave of information technology revolution. The number of RFID applications in different industries is increasing continuously. Cumulative sales of RFID tag is up in 2006 which shows RFID adoption trend in industries to improve their efficiency of operations and to gain a competitive advantage. In the aviation industry, major airports, airlines have been also planning the RFID adoption in baggage handling and customer services areas for a long time. Many pilot tests have been performed at various airports and RFID tags were found to be far more precise along with better performance than bar codes. This paper provides a review on RFID systems, associated technology, advantages, limitations and applications in various fields. Further, this paper reports the preliminary review of state of RFID adoption planning, architecture and implementation plan in a major airline, focusing on improved baggage handling, increased airport/airline security and customer services.KEYWORDS: aviation, airline, baggage handling, customer-service, Radio Frequency Identification (RFID)